Root moisture saturation as a stress factor in zucchini (Cucurbita pepo) (Research, Society and Development, 2020)
The Summer squash, is another vegetable used for hydroponics exploration. Also, little is known about its behavior under conditions of saturation of the root system that impose hypoxia or anoxia, a factor recognized by the high potential stressor. Thus, the responses of the Caserta cultivar to the flooding of the root in a 50% shade in Teresina/PI between September and November 2018 were evaluated. The experimental design was randomized blocks with 3 replicates, with plots constituted of a vase with 02 plants, and the treatments represented by times of flood of the root: 00; 24; 48 and 72 hours, applied at the true leaf stage, 14 days after emergence. The flood showed to be an impressive stress factor, which in 24 hours caused wilt of the plant, affected the weight of the fresh matter of the root, of the aerial part and relation aerial part/root; Anticipated the closure of the male flowers, compromising the anthesis of female flowers, reducing the number of male and female flowers. Despite the occasional lenticella differentiation the summer squash can withstand a maximum of 24 hours of flooding, so that exposure to longer times will lead to irreparable damage.